Integrating museum collections and molecules reveals genus-level synonymy and new species in red devil spiders (Araneae, Dysderidae) from the Middle East and Central Asia - Bellvert, Adrià; Dimitrov, Dragomir; Zamani, Alireza; Arnedo, Miquel A. (European Journal of Taxonomy, 2024)
This paper reviews little-known species of the dysderid spider genera Dysdera Latreille, 1804, and Dysderella Dunin, 1992 based on specimens collected in the Caucasus, Middle East, and Central Asia. After combining molecular phylogeny of five mitochondrial and three nuclear genes with morphological evidence, Dysderella is proposed as a junior synonym of Dysdera. In addition, three species are described as new to science: D. jaegeri Bellvert & Dimitrov sp. nov., D. naouelae Bellvert & Dimitrov sp. nov., and D. kourosh Bellvert, Zamani & Dimitrov sp. nov. Four combinations are proposed: Dysdera caspica Dunin, 1990 comb. rev., Dysdera transcaspica Dunin & Fet, 1985 comb. rev., Dysdera elburzica (Zamani, Marusik & Szűts, 2023) comb. nov. and Dysdera sancticedri (Brignoli, 1978) comb. nov. (ex. Dasumia Thorell, 1875). Furthermore, we report a first record of D. festai Caporiacco, 1929 in Turkey and its male cheliceral polymorphism. Our results illustrate the deficiencies that undermine the current taxonomy of this genus. For example, many species are described based on only one or few specimens or limited locality data. The advancements in DNA sequencing technologies applied to museum specimens reduce the need for fieldwork collection and export of fresh specimens. This highlights the significance of museum collections for improving research in this field.